Analisis Perbandingan Webqual dan E-Servqual Terhadap Website PMB ITTP - Tarigan, Emya Ninta; Dedy Agung Prabowo; Resad Setyadi (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
New Student Admission Website is one of the services to register online to become a student at the Telkom Institute of Technology Purwokerto. This research was conducted to Comparative Analysis of Webqual and E-Servqual methods on the New Student Admission (PMB) website of the Telkom Institute of Technology. In the development of the PMB website, there are shortcomings felt by prospective new students regarding features that are not used by the PMB unit of IT Telkom Purwokerto, but still appear when registering for new student admissions. both methods, it is found that the analysis of WEBQUAL and E-SERVQUAL methods is interrelated in improving the quality of service interaction. Factors such as reputation, information security, personalization, community space, ease of communication, and responsiveness to user problems play an important role in creating a good interaction experience for PMB ITTP website users.